2022
DOI: 10.3390/genes13112161
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Growth and Photosynthetic Traits of Polyploid Poplar Hybrids and Clones in Northeast China

Abstract: To evaluate differences among 19 different ploidy hybrid poplar clones grown in northeast China, 21 traits related to growth traits and photosynthetic characteristics were detected and analyzed. Abundant phenotypic variations exist among and within populations, and these variations are the basis of forest tree genetic improvements. In this research, variance analysis showed that the traits except the net photosynthesis rate among the different ploidies and all the other traits exhibited significant differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The interaction between RCD and SH will make it possible to predict the quality indicators of the seedlings: for example, the seedling sturdiness quotient (SH RCD-1) included in the Dickson Quality Index [55] as well as the possibility of excluding the operation of measuring the height of the seedling using only the RCD measurement. Moreover, a close correlation between these indicators, as shown in a recent study by Jiang et al [56], may contribute to the selection of the best trees. Another possibility is the one shown in Rodríguez de Prado et al [57], the height-diameter (H-D) ratio, which, due to the strong correlation between the two, can be "an important tool for estimating the height of trees in mixing forest at various spatio-temporal scales".…”
Section: Discussionmentioning
confidence: 70%
“…The interaction between RCD and SH will make it possible to predict the quality indicators of the seedlings: for example, the seedling sturdiness quotient (SH RCD-1) included in the Dickson Quality Index [55] as well as the possibility of excluding the operation of measuring the height of the seedling using only the RCD measurement. Moreover, a close correlation between these indicators, as shown in a recent study by Jiang et al [56], may contribute to the selection of the best trees. Another possibility is the one shown in Rodríguez de Prado et al [57], the height-diameter (H-D) ratio, which, due to the strong correlation between the two, can be "an important tool for estimating the height of trees in mixing forest at various spatio-temporal scales".…”
Section: Discussionmentioning
confidence: 70%
“…Prior studies have laid the foundation for plant breeding by exploring genetic associations between traits, evaluating parental combining effects, and analyzing phenotypic and genetic variations [ 18 , 19 ]. Recently, researchers have delved deeper into understanding the specific roles of genotype and environmental factors in phenotypic expression and genetic variation using more advanced and refined methods [ 20 ]. While these studies have offered valuable insights, there remain unresolved issues and challenges in the specific application of Juglans mandshurica .…”
Section: Introductionmentioning
confidence: 99%
“…Polyploids, which are organisms with three or more complete sets of chromosomes, are widespread among angiosperms [ 1 , 2 , 3 ]. Many previous studies have shown that polyploidization leads to considerable changes in the morphology, physiology, and biochemistry of plants and is a key driver of macro-evolutionary success [ 3 , 4 , 5 , 6 ]. Specifically, polyploidization has been shown to change plants’ height [ 7 , 8 , 9 ], leaf index [ 10 ], fruit size [ 11 , 12 ], and secondary metabolite levels [ 13 , 14 ], among others.…”
Section: Introductionmentioning
confidence: 99%